2003
DOI: 10.1093/nar/gkg519
|View full text |Cite
|
Sign up to set email alerts
|

GlobPlot: exploring protein sequences for globularity and disorder

Abstract: A major challenge in the proteomics and structural genomics era is to predict protein structure and function, including identification of those proteins that are partially or wholly unstructured. Non-globular sequence segments often contain short linear peptide motifs (e.g. SH3-binding sites) which are important for protein function. We present here a new tool for discovery of such unstructured, or disordered regions within proteins. GlobPlot (http://globplot.embl.de) is a web service that allows the user to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
800
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 917 publications
(822 citation statements)
references
References 35 publications
17
800
0
5
Order By: Relevance
“…FoldIndex and GlobPlot2.3 were used to assess the propensity to form secondary and tertiary structures (55,56). The default parameter for window size in FoldIndex was changed to 10 residues, to be comparable with GlobPlot2.3.…”
Section: Structure Assessmentmentioning
confidence: 99%
“…FoldIndex and GlobPlot2.3 were used to assess the propensity to form secondary and tertiary structures (55,56). The default parameter for window size in FoldIndex was changed to 10 residues, to be comparable with GlobPlot2.3.…”
Section: Structure Assessmentmentioning
confidence: 99%
“…Assignment of the best repeats and registers, compilation of amino acid occupancies and charge pairs were performed with Perl scripts, coupled with manual intervention for the identification of register-shifts. We used the JNet secondary structure prediction method (Cuff et al, 1998), via the JPred web server, and the GLOBPLOT (Linding et al, 2003) tool for predicting disordered regions. Amino acid composition of domains was calculated with the COMPSEQ program of EMBOSS.…”
Section: Sequence Analysis Feature Predictions and Statisticsmentioning
confidence: 99%
“…Low complexity sequences were shown to be absent from globular regions of structured proteins in the Protein Data Bank (PDB) 18,23 . More recently, several other groups have developed predictors of disordered or similar regions [24][25][26][27] each of which has particular advantages.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, we combine both collapsed-disorder (molten globule-like) and extended-disorder (random coil-like) into a single disorder category, while others regard molten globules as partially folded and not in the natively unfolded category. Predictors of coil regions with high B-factors, called hot-loops, have also been developed 26,27 . Our studies showed that the amino acid compositions of high B-factor regions are distinct from those of disordered regions, and these distinctions were used to develop a predictor of high B -factor regions 28 .…”
Section: Introductionmentioning
confidence: 99%